Impact of Green Thinking in Achieving Sustainability in Business: A Case Study of Godrej Consumer Products Limited - Khandelwal, Shidhanshu (My University, 2024)
This thesis examines the relationship between corporate sustainability and green thinking techniques, using Godrej Consumer Products Limited (GCPL) as a case study. This study examines the significance of green initiatives, their impact on sustainability performance, and the underlying factors influencing their effectiveness through a thorough analysis involving surveys and interviews, including responses from 42 survey participants and 2 interviewees. The results provide detailed understandings of resource optimization, operational improvement, and reduction of environmental effect. According to 94% survey participants, GCPL exhibits a strong commitment to sustainability despite obstacles like organizational inertia and resource limitations through programs like waste minimization and the deployment of renewable energy. Looking more closely at certain results, 88% of respondents emphasize how important it is to utilize renewable energy to cut carbon emissions and improve operational efficiency. Furthermore, according to 92% of respondents, waste minimization techniques are critical for maximizing resource use and minimizing environmental impact. This research adds a great deal to the body of knowledge already in existence and provides practical advice on how to use green practices in corporate settings. It offers a thorough conceptual model to interpret the complexities of sustainability dynamics in the corporate environment by fusing academic frameworks with actual data. This study adds to our knowledge of how sustainable business practices are supported by green thinking and offers useful advice to researchers, policymakers, and practitioners alike. It provides firms with useful avenues for promoting sustainability efforts and navigating the changing terrain of ethical business practices by outlining particular findings and survey responses.
Keywords: enterprises; sustainable development; green economy; societal responsibility; case study; renewable energy sources; environmental responsibility; business operations; fi=Kansainvälinen liiketoiminta|en=International Business|; Master's Degree Programme in International Business